Addressing unmet needs in pregnancy and family planning of people living with rare and low-prevalence diseases: results of the “ERN transversal working group on pregnancy and family planning” survey - Fulvio, Giovanni; Marinello, Diana; Zucchi, Dina; Aguilera, Silvia; Benachi, Alexandra; Biller, Ruth; Blanco, Ignacio; Boiteux, Marie Claude; Borgards, Petra; Brandi, Maria Luisa; Costafreda, Ester; Fonseca, João E.; et al. (Reproductive Health, 2025)
Background: Pregnancy and family planning for individuals living with rare and low prevalence diseases present unique medical, psychological, and logistical challenges. The European Reference Networks (ERNs) were established to address healthcare disparities and enhance patient care for rare diseases across Europe. The ERN Transversal Working Group on Pregnancy and Family Planning was created to identify common unmet needs and to develop targeted actions to improve healthcare delivery. As part of this initiative, a survey was conducted to gather insights from patients, caregivers, and family members about their experiences and challenges related to pregnancy and family planning. Methods: The survey was co-designed by healthcare professionals and patient representatives from 20 ERNs. It covered various domains, including fertility preservation, pre-conceptional counselling, psychological support in the pre-conceptional counselling, pre-implantation diagnosis, prenatal diagnosis, family planning, pregnancy monitoring, post-pregnancy monitoring, lactation and newborn management. The survey, available in multiple languages, was distributed via online platforms between February and July 2022. Quantitative responses were analysed descriptively, while qualitative data from open-ended questions were processed using word frequency analysis. Results: A total of 769 responses were collected, with 574 from patients and 155 from caregivers. The majority of respondents were female (90%) and aged 31–40 years, primarily from Germany, France, Spain, and Italy. The most pressing concerns identified included lack of access to accurate medical information, limited psychological support, inadequate pre-conceptional counselling, and challenges related to pregnancy monitoring and postpartum care. The need for multidisciplinary healthcare teams and improved education on reproductive health was emphasised. Word frequency analysis highlighted key concerns, with “inform,” “support,” and “risk” being the most recurrent terms. Conclusions: This study underscores the widespread need for comprehensive, patient-centred approaches in pregnancy and family planning for individuals with rare and low prevalence diseases. Improved access to specialised healthcare teams, psychological support, and clear, standardised medical information is essential. These findings advocate for the development of harmonised European policies and multidisciplinary strategies to enhance reproductive healthcare. Plain english Language summary: People living with rare diseases often face extra challenges when it comes to pregnancy and family planning. To better understand these issues, a group of experts and patient representatives from 20 European Reference Networks (ERNs) worked together to conduct a survey. A European survey of 769 people, mostly women aged 31 to 40 from Germany, France, Spain, and Italy, revealed significant gaps in care. The most common concerns shared by patients included difficulty finding clear medical information, not enough psychological support, gaps in counselling, and challenges with checking on health during and after pregnancy. Many felt that better teamwork among different healthcare providers and improved education on reproductive health would make a big difference. In summary, this study underscores the urgent need for better reproductive healthcare for people with rare diseases.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Patient-centered care european reference networks (ERN); Pregnancy; Psychological support; Rare diseases; Reproductive health; Unmet needs